Origin And History Of Aloe Plant - Nasritdinov Ahmadjon Abdukhamidovich; Sadullaeva Rukhshona (Genius Journals, 2024)
The origin, species and varieties of aloe plant were studied, research was conducted, the importance of aloe plant in medicine, medicine, cosmetics and landscaping, prospects and unique properties of growing aloe plant, the importance of ecological landscaping.
Keywords: Natural medicinal plant; species of aloe plant; flavonoids